Philantropinum in Kunvald – the regional school in the early 19th century - Lubomír Vojtěch Baar (In Gremium. Studies in History, Culture and Politics, 2022)
The owner of the Kunvald Château, the countess Maria Walburga, attempted to copy and improve the concept of Dessau Philanthropinum and inspired herself in the works of J. B. Basedow. She established her own Philantropinum in Kunvald village between 1792 and 1814. It is an interesting example of a school based on ideas from the late Enlightenment and Philanthropy, where children studied regardless of their gender, religion, or social status.The Philanthropinum in Kunvald employed various modern methods, and was exceptionally religiously tolerant. This article tries to summarize basic information about Kunvald/Kunín and its surroundings; to briefly introduce families that owned the château, and the main goal of this article is to aptly describe the schedule and regimen of the Kunvald Philanthropinum.